Evaluation of FRAX in patients with periprosthetic fractures following primary total hip and knee arthroplasty - Lukas A. Holzer; Lisa Borotschnig; Gerold Holzer (Scientific Reports, 2023)
Abstract The fracture risk assessment tool (FRAX) is a tool which calculates an individual 10-year fracture risk based on epidemiological data in patients with a risk of osteporosis. The aim of this study was to evaluate the value of FRAX to estimate the risk of postoperative periprosthetic fractures (PPF) in patients following with total hip and knee arthroplasty. 167 patients (137 periprosthetic fractures in total hip arthroplasty and 30 periprosthetic fractures in total knee arthroplasty) were included in this study. Patients’ data was retrieved retrospectively. In each patient the 10-year probability of a major osteoporotic fracture (MOF) and an osteoporotic hip fracture (HF) was calculated using FRAX. According to the NOGG guideline 57% of total hip arthroplasty (THA) patients and 43.3% of total knee arthroplasty (TKA) patients were in need of osteoporosis treatment, whereas only 8% and 7% received an adequate one respectively. 56% of the patients with PPF after THA and 57% of the patients with PPF after TKA reported about a previous fracture. Significant associations between the 10-year probability of a MOF and HF calculated by FRAX and PPF in THA and TKA were seen. The results of the present study show that FRAX might have the potential to estimate the PPF in patients following THA and TKA. FRAX should be calculated before and after THA or TKA in order to assess the risk and counsel patients. The data show a clear undertreatment of patients with PPF in respect to osteoporosis.